A MODEL FOR COMPUTER SUPPORTED COLLABORATIVE LEARNING - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2010)
There can be different definitions of collaborative learning. One of the may be; Cooperative learning is a successful teaching strategy in which small teams, each with students of different levels of ability, use a variety of learning activities to improve their understanding of a subject. Each member of a team is responsible not only for learning what is taught but also for helping teammates learn, thus creating an atmosphere of achievement. (U. S. Dept. of Ed. Office of Research, 1992). The other definition may be; Collaborative learning is based on the idea that learning is a naturally social act in which the participants talk among themselves (Gerlach, 1994). In recent years collaborative learning system performs with the support of computers. With technological improvements it is required to use collaborative learning tools with computer support for raising the positive effects on learning. It carried some problems in adoption to this technology. So new learning model needs were exposed. Computer-supported collaborative learning (CSCL) is a method of supporting collaborative learning using computers and the Internet. It is related to Computer Supported Cooperative Work (CSCW) and research in psychology, computer science, and education. If Collaborative learning is the idea of bringing together learners to work and learn in a collaborative manner, then Computer Supported Collaborative Learning tools complete this task synchronously or asynchronously. Online collaborative tools provide a central locale for these types of communications. The technology allows individuals who are far apart to collaborate on-line. The use of these tools is increasing, however many trainers are still new to what tools are available on the Internet and how to use them effectively. In the first part this study details some of the tools available and suggests ways to use them to promote online learning and the collaboration of students. Main focus is on how people learn in the context of collaborative activity and how to design the technological settings for collaboration. I have to define what type of collaborative learning is needed at what timing. In the second part the study suggests a collaborative learning support model, shows the basic design of the knowledge model, and argues collaborative learning support from a common perspective.
Keywords: CSCL; CSCW; collaborative tools; collaborative learning